Europe’s Values for the Future - Raluca Mihalcioiu (Journal of Danubian Studies and Research, 2013)
The EU has been misunderstood as a purely economic community for a long time. It should not be forgotten that the EU is a community of values in the first place even if the EU's economy plays an important role for the whole World. The crisis has a firm grip on Europe. Every day there are more and more comments of those who have already predicted the downfall of the EU. The value of our common currency and even more the importance of our shared values of Europe appear to be in free fall. The Treaty on European Union (as amended by the Lisbon Treaty) mentioned these values in Article 2. These values are common to all Member States with a society, which is characterized by pluralism, non-discrimination, tolerance, justice, solidarity and equality between women and men. “Europe has become a role model. The universal appeal of our values is reflected in the countries of our southern and eastern neighbors. Unlike in the past, these values are not mediated by subjugation and colonization, but by voluntary acceptance when we share them. This applies to our community. This also applies to our relationship with our neighbors and the world. The purpose of this paper is to describe the most fundamental European values as well as their significance for our society. It shows why these values are the basis for our modern and democratic societies today. The paper points out how these values are going to be like in the future, during the deepest crisis of the EU.